Synthesis and Properties of Polymer Metal Complexes of Polygalacturonic Acid With d-Metal Ions - Mokhira Nurmatova; Khusnigul Sabirova; Sayora Rashidova (International Journal of Polymer Science)
In this work, novel copper (Cu) (II), cobalt (Co) (II), and zinc (Zn) (II) polymer-metal complexes were synthesized from polygalacturonic acid (PGA) isolated from the “F-2 Yubileiny” lemon pectin. The structure of complexes was studied by XRD analysis. The IR spectrum of PGANaCu at pH 3.5 shows asymmetric (νas) and symmetric (νsym) carboxylate groups (COO-) bands shifted to 1611 and 1415 cm−1. The absorption of carboxyl groups at 1617 cm−1 is increased when compared to PGA, indicating the exchange of the hydrogen in the carboxyl group with Cu(II) ions. The metal ions at low concentrations bind to carboxyl groups of the polymer through Langmuir adsorption mechanisms being titrated with sodium salt solution, forming a cross-linked structure known as the “egg-box” model. The toxicity of the obtained salts was studied, and it was found that the compounds can be classified as moderate or slightly toxic. Moreover, metal complexes possess a broad spectrum of antimicrobial activity against gram-positive and gram-negative bacteria. These findings and the average molecular weight of basic metal-PGA complexes offer valuable discoveries in the design of complexes with specific metal-releasing properties.